2021
DOI: 10.3390/land10020144
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Use and Abuse of Nature in Catalonia with Proposals for Sustainable Management

Abstract: This paper provides an overview of the last 40 years of use, and in many cases abuse, of the natural resources in Catalonia, a country that is representative of European countries in general, and especially those in the Mediterranean region. It analyses the use of natural resources made by mining, agriculture, livestock, logging, fishing, nature tourism, and energy production and consumption. This use results in an ecological footprint, i.e., the productive land and sea surface required to generate the consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Demographics, land-use and, climate and global change scenarios forecast a decline in freshwater supplies and an increase in water demand, especially in the Mediterranean basin [18]. Over the previous 50 years, a decline in river discharges has been observed in Spain and it has been shown that this decline was due to an expansion of shrubs and forests in formerly cultivated areas [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographics, land-use and, climate and global change scenarios forecast a decline in freshwater supplies and an increase in water demand, especially in the Mediterranean basin [18]. Over the previous 50 years, a decline in river discharges has been observed in Spain and it has been shown that this decline was due to an expansion of shrubs and forests in formerly cultivated areas [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies include forest management within the watershed scale, and water use and management based not only on efficient water consumption and water supply infrastructure but also on a more sustainable use of the land. [18,75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the models of climatic change ( González-Hidalgo et al, 2009 ; Peñuelas et al, 2021 ) for the Mediterranean area forecast more irregularity in precipitation patterns, specifically more rainfall in autumn than in spring, and concentrated over a few days in some years, while in others, there will be heavy droughts. Air temperature is rising ( Vicente-Serrano et al, 2014 ) and in the Montseny the variation in the average air temperature in Turó de l’Home (1,712 m a.s.l.)…”
Section: Introductionmentioning
confidence: 99%